INTERNATIONAL CHARITABLE ORGANIZATIONS: ESTABLISHMENT, DEVELOPMENT AND FEATURES OF FUNCTIONING - Петро ПІДСАДНЮК (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The article is dedicated to the study of the peculiarities of charity development and the functioning of international charitable organizations that have acquired the status of an international entity. Such non-governmental actors are able to respond adaptively and act more quickly and locally on the world stage to address the most pressing issues, providing assistance and support to the most vulnerable categories and in the most critical geopolitical spaces. With the help of an interdisciplinary approach, it was possible to identify the historical background of the origin of the phenomenon of selfless human activity, a systematic political and legal analysis of international and domestic legislation helped to identify the peculiarities of the functioning of international charitable organizations in the United States, Europe and Ukraine, and a generalization of the obtained results crystallized the foundations and features of their direct involvement in problem areas. The difference between international non-governmental organizations and international charitable organizations was proved. The author identifies the main sources of funding for such structures through grants, donations from individuals and legal entities, international organizations and governments. It is established that the tasks of establishing and operating international charitable organizations are implemented in three areas of activity, including non-refundable assistance, administration of response and recovery projects, lobbying and actualization of the problem for the world community through influence on the political establishment and public opinion.